Lexicographic Data on Dialects in the Lithuanian Language Resources Information System E-Language - Urbanavičienė, Jolita (Lietuvių kalba, 2022)
The article presents the Lithuanian Language Resources Information System E-Language, with a focus on those resources which include the lexicographic data on dialects: The Dictionary of the Lithuanian Language (DLL) and its three catalogues, namely The Main Catalogue, The Catalogue of New Additions, and The Catalogue of Dialects. The article addresses the modernized structure of the data from these lexicographic resources and its search system and discusses the problems faced by the developers of the system and their solutions. It is concluded that the development of E-Language marked a quantitative and qualitative improvement of its predecessor, the Lithuanian Language Resources Information System (LLRIS), which came to life in 2015: it was modernized on both a quantitative level (by integrating 3 dictionaries and 1 catalogue into the information system and creating 7 services) and a qualitative level (the availability, usability and integrity of Lithuanian language resources were improved). E-Language development process also accelerated the advancement of other electronic products and services: it contributed to solving the systemic problems of the Lithuanian font Palemonas, encouraged the appearance of the keyboard layout known as the Copenhagen Transcription, etc. One of the further tasks for the improvement of the information system E-Language could be the quantitative addition of integrated resources, as only a small part of the catalogues of The Dictionary of the Lithuanian Language is digitalized.